THE EFFECTIVENESS OF PEER EDITING TO IMPROVE THE STUDENTS’ ESSAY WRITING SKILL - Tusino, Tusino (Universitas Muhammadiyah Surakarta, 2013)
This study was aimed at revealing students? essay writing skill, describing the improvement of writing aspects, and finding out whether or not the use of peer editing was effective to improve the students? writing skill. This reseach was experimental study using nonequivalent control group design. The population of this research was all the fifth semester students of English Education Program of Muhammadiyah University of Purworejo. The researcher used two classes as the research samples. As the experimental group, the researcher took students of VA class who were taught by peer editing. Then, the researcher involved students of VB class as the control group. The reseacher conducted a series of treatment from August to November 2014. The researcher used a writing test to collect the data. Descriptive statistics and inferential statistics were employed to analyze the data. After analyzing the data, the researcher obtained some find- ings. First, the students? writing score was 71.2 belonged to good category. Second, all writing aspects could improve where the significant improvement was in the aspects of content (2.6 points) and vocabulary (1.9 points). The aspects of organization, grammar, and mechanics did not increase significantly (0.3-0.7 points). Third, the result of calculation illustrated that t-obtained was higher than the critical value on the t-table (3.602>2.000). It meant that the use of peer editing was effective to improve the students? essay writing skill.